2014
DOI: 10.1097/brs.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and Thoracic Sagittal Misalignment After Surgery for Adolescent Idiopathic Scoliosis

Abstract: Independent of the surgical technique used, the cervical spine had a tendency to decompensate and acquire a kyphotic sagittal profile. Constructs based on all pedicle screws have a stronger hypokyphotic effect on the thoracic spine, with a predisposition to greater decompensation of the cervical spine. Kyphotic changes in the C2-C7 sagittal alignment induced by scoliosis correction are correlated with the level of the upper-instrumented vertebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
27
1
2
Order By: Relevance
“…Similar relations were also found in some recent studies [1113]. Thereafter, Legarreta et al [14] found that both pedicle screws and hybrid instrumentation (hooks and pedicle screws) have a hypokyphotic effect on the thoracic spine, which could lead to the occurrence of CK after the surgery, especially in cases in which the upper instrumented vertebra (UIV) is above the T4 level. However, Yanik et al [15] indicated that the postoperative CK was correlated with the decreased TK and T1 slope, nor UIV level.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar relations were also found in some recent studies [1113]. Thereafter, Legarreta et al [14] found that both pedicle screws and hybrid instrumentation (hooks and pedicle screws) have a hypokyphotic effect on the thoracic spine, which could lead to the occurrence of CK after the surgery, especially in cases in which the upper instrumented vertebra (UIV) is above the T4 level. However, Yanik et al [15] indicated that the postoperative CK was correlated with the decreased TK and T1 slope, nor UIV level.…”
Section: Introductionsupporting
confidence: 76%
“…Both pedicle screws and hybrid instrumentation (hooks and pedicle screws) have a hypokyphotic effect on the thoracic spine, which could lead to the occurrence of CK after the surgery [14, 18]. In this study, all 50 patients underwent surgical treatment with 1-stage posterior pedicle-screw correction and fusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently there are no published studies that document the actual incidence of these long-term degenerative complications. However, anecdotal clinical evidence suggests that many years after surgery there are increasing numbers of patients with disabling mechanical back pain secondary to degeneration at the junctional levels [6] . Eventually, further fusion surgery may be required to treat these patients.…”
Section: Introductionmentioning
confidence: 99%